Chromosomal aberrations in the tumor and peripheral blood and changes in aberrations during treatment of canine lymphoma - Devitt, Jennifer J., author; LaRue, Susan M., advisor (Colorado State University. Libraries, 2008)
Lymphoma is the most frequently diagnosed hematopoietic malignancy in dogs. Untreated, the survival times are approximately one month. Chemotherapy is the current standard of care and can initiate and temporarily maintain remission, with average survival times of one year. Cytogenetic abnormalities can aid in diagnosing tumors as well as in giving a more accurate prognosis for the specific mutations present. In human lymphoma patients, chromosomal changes from peripheral lymphocytes have been used prognostically and to document response to treatment. Evaluating peripheral lymphocytes instead of tumor cells is less invasive for the patient and technically easier. Recurrent aberrations have been reported in canine lymphomas. Since this cancer parallels human Non-Hodgkin's Lymphoma which has recurrent chromosomal anomalies that have been correlated with clinical behavior of the tumor and patient survival, it reasons that canine lymphoma would as well. This study was designed to investigate a correspondence between numerical aberrations detected in the tumor and the peripheral blood in dogs with lymphoma. Additionally, the peripheral blood aberrations were monitored during the course of treatment to document changes seen during remission and at the time of disease recurrence. Twenty-five dogs with lymphoma had one lymph node excised, a peripheral blood sample drawn, and a bone marrow aspirate performed. A portion of the lymph node was submitted for histopathology and immunophenotyping and another portion was retained for cytogenetic analysis. The peripheral blood sample was cultured for chromosome counting and cytogenetic analysis. The bone marrow aspirate was used for staging purposes. A significant correspondence between the numerical aberrations in the tumor and the peripheral blood was found with six out of the seven numerical aberrations demonstrating predictive value of the peripheral blood. During the course of treatment, the quality and quantity of aberrations changed, likely due to DNA damaging treatment modalities. Once treatment ended, the frequency of aberrations diminished. A prognostic significance could not be determined using the additional diagnostic information that was garnered such as age, gender, histological classification, breed, immunophenotype, or stage of disease. This was probably due to a limited sample size and is worthy of further investigation.
Keywords: canine lymphoma; chromosomal aberrations; cytogenetics; lymphoma; cellular biology; physiology; veterinary services